Estrategias didácticas cognitivas para la construcción de aprendizajes significativos en Biología. Año lectivo: 2023-2024 - Reyes Quizhpe, Valeria Stefania (2024)
The implementation of cognitive didactic strategies in the development of the teaching-learning process, promotes the construction of significant learning in students; for this Curricular Integration Work, the objective was: To promote the construction of significant learning in students, through the application of cognitive didactic strategies that allow awakening their interest to participate in the development of the teaching-learning process of Biology in the second year of GUB, of "Daniel Álvarez Burneo" Educative Unit; academic year 2023-2024. The research method used was inductive, based on direct observation, which allowed identifying the lack of interest on the part of the students to get involved in the development of the Biology TLP, which generates negative effects in the construction of significant learning in them; through bibliographic research, cognitive strategies were determined to improve the identified reality; the approach was qualitative; relevant characteristics of the classroom process were determined in order to influence them. According to the nature of the information, it corresponds to a Participatory Action Research. Given that both the research subjects (students) and the researcher were involved in actions to change the identified reality; according to the temporality, it is transversal, due to the short period in which the research was carried out. After the application of the evaluation and research instruments, the results show that the implementation of cognitive didactic strategies, such as: organization of information, elaboration strategies, repetition strategies and information retrieval, promote the participation of students in the development of the TLP and improve the understanding of the contents of the subject. Finally, it is concluded that cognitive didactic strategies motivate students to participate in the development of the teaching-learning process of Biology and enhance the construction of meaningful learning in them. Key words: teaching-learning process - motivation - academic performance - active participation.